METRONIDAZOLE INDUCES SIGNIFICANT PATHOLOGICAL ALTERATIONS IN THE MALE REPRODUCTIVE SYSTEM OF MICE - Al – Timimi, Z. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The present study was aimed to investigate the possible effects caused by the antibiotic, metronidazole, on the histology of the testis and the morphology of the sperms of mice. To achieve this,  adult male albino Swiss Mice were orally administrated with 0.1 ml (100 mg\ kg ) of the commercially used metronidazole (Flagyl) for 60 consecutive days. The results showed significant decreases (p